2003
DOI: 10.1117/12.487623
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic neural networks for infrared imaging target discrimination

Abstract: The next generation of infrared imaging trackers and seekers will allow for the implementation of more sophisticated and smarter tracking algorithms, able to keep a positive lock on a targeted aircraft in the presence of countermeasures such as decoy flares. Pattern recognition algorithms will be able to select targets with the help of features extracted from all possible targets images observed in the missile's field of view. Artificial neural networks provide an important class of such algorithms. In particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…The last column gives a reference to that technology However, because the focal plane array imaging seekers represent the latest developments in IR missile seeker technology, no information is publicly available about the particular image processing and pattern recognition algorithms they use. The present study can be seen as the continuation of that in Cayouette's MSc thesis [7] and Cayouette et al [8] that considered the same aircraft-flare discrimination problem we deal with here. This former study used a probabilistic neural network [66] to classify the patterns, seen in a single infrared video frame, as corresponding to aircrafts or flares.…”
Section: On Infrared Missile Seekersmentioning
confidence: 80%
“…The last column gives a reference to that technology However, because the focal plane array imaging seekers represent the latest developments in IR missile seeker technology, no information is publicly available about the particular image processing and pattern recognition algorithms they use. The present study can be seen as the continuation of that in Cayouette's MSc thesis [7] and Cayouette et al [8] that considered the same aircraft-flare discrimination problem we deal with here. This former study used a probabilistic neural network [66] to classify the patterns, seen in a single infrared video frame, as corresponding to aircrafts or flares.…”
Section: On Infrared Missile Seekersmentioning
confidence: 80%
“…The features selected for this work were not typical or commonly used features such as SIFT, FAST, SURF, Hu or Hough Moments discussed in Section 2.2, but rather a unique set of features that were previously used in another classification study using thermal imagery only [28]. In Cayouette et al's study, classification rates between 95% and 99.43% were achieved using only two classes of objects (aircraft and flare) that clearly differentiated from each other.…”
Section: Further Improvementsmentioning
confidence: 91%
“…Cayouette, Labonté and Morin [28] [29] continued the work previously started with Cayouette [28] on the use of PNN to discriminate target aircraft and flares in static images. In the follow-up study, Labonté and Morin considered the time evolution of the image features from a series of frames.…”
Section: Image Featuresmentioning
confidence: 99%
“…More specifically, we explore the ability of an artificial neural network to discriminate between targets. In a first study, Cayouette, Labonté and Morin [4] have shown that a neural network that uses only the static features of the scenes, i.e. those measured in a single video frame, can identify aircrafts and flares with a success rate of over 95%.…”
Section: Problem Considered and Solutionmentioning
confidence: 99%